The Influence of School Principal Leadership, Emotional Intelligence, and Teacher Well-being on Teacher Performance - Khairunnisa, Dinda; Hendra, Robi; Pratama, Linardo (Indonesian Educational Administration and Leadership Journal (IDEAL), 2025)
This study aims to examine the influence of school principal leadership, emotional intelligence, and teacher well-being on teacher performance at State Senior High School 4 in Jambi City. The research uses a quantitative method with a survey approach. Data analysis was conducted using the SmartPLS application. The population in this study consists of all the teachers at State Senior High School 4 in Jambi City, with a total of 75 teachers as the research sample. The results show that school principal leadership has a significant positive effect on teacher performance, with a p-value of 0.000 < 0.05 and T-statistics of 9.308. Emotional intelligence has a significant positive effect on teacher performance, with a p-value of 0.016 < 0.05 and T-statistics of 2.406. Teacher well-being has a significant positive effect on teacher performance, with a p-value of 0.000 < 0.05 and T-statistics of 4.462. Additionally, there is a significant joint effect from the variables of school principal leadership, emotional intelligence, and teacher well-being on teacher performance, with an R-squared (R²) value of 0.570 and an adjusted R-squared value of 0.567.   Keywords: School principal leadership, emotional intelligence, teacher well-being, teacher performance